Exposure of Screen Time in Relationship with Obesity in Junior High School Adolescence in Yogyakarta - Nurul Putrie Utami; Martalena Br Purba; Emy Huriyati (Jurnal Dunia Gizi, 2018)
Obesity has been increasing throughout the world that also will impact to the increasing of non communicable disase realated to obesity. Obesity which is occurred since adolescence can worsen the problem because it will carry over until adult so it was necessary to prevent obesity by controlling the obesity risk factor. Some studies reveal that increasing obesity was emerged because of high screen time. Too much screen time can increase exposure of unhealthy snack and increase sedentary activity that was obesity risk factor. Objectives; to determine the relationship of screen time and obesity in adolescent in Junior High School in Yogyakarta. Material and Method; the type of research used was observational with a case control study approach. This research was conducted in 4 junior high schools in the city of Yogyakarta. The sample of this study was 120 students aged 12-15 years consisting of 60 students in the case group and 60 students in the control group selected by the proportionate random sampling method which then matched age and sex. Results; in this study it was found that there was a significant relationship between screen time of more than 2 hours/day and the risk of obesity in adolescent junior high school in Yogyakarta City (p=0.019) with an Odds Ratio of 2.6 (1.160-5.750). Higher screen time is significantly associated with a higher level of energy intake (p=0.037) with a Prevalence Ratio of 1.3 (1.025-1.638). Conclusion; it was found that there was a relationship between screen time and obesity in adolescent junior high school in Yogyakarta City.